2017
DOI: 10.4103/neuroindia.ni_814_16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surgical risk factors in the development of ventilator-associated pneumonia in neurosurgical intensive care unit patients: Alarming observations

Abstract: The incidence of VAP is high. Patients of aneurysmal SAH are at higher risk and VAP is as common in patients with supratentorial lesions as in those with infratentorial pathologies. The increase in resistance to the commonly used antibiotics is a cause for concern. Efforts should be taken to evolve more effective preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…As previously reported, the mortality rate of meningitis/encephalitis in post-neurosurgical patients ranges from 15% to 35%, 20,21 and consistent with these prior studies, the total in-hospital mortality rate for the diagnosis of Enterobacteriaceae meningitis/encephalitis in our study was 23.2%. Many previous studies have only shown the risk factors of neurosurgical infection, which include percentage of males, CSF leakage, surgical diagnosis, surgeon, early reoperation, surgical duration, EVD, LD, diabetes, and so on.…”
Section: Discussionsupporting
confidence: 92%
“…As previously reported, the mortality rate of meningitis/encephalitis in post-neurosurgical patients ranges from 15% to 35%, 20,21 and consistent with these prior studies, the total in-hospital mortality rate for the diagnosis of Enterobacteriaceae meningitis/encephalitis in our study was 23.2%. Many previous studies have only shown the risk factors of neurosurgical infection, which include percentage of males, CSF leakage, surgical diagnosis, surgeon, early reoperation, surgical duration, EVD, LD, diabetes, and so on.…”
Section: Discussionsupporting
confidence: 92%
“…MiR‐1247 could inhibit LPS‐induced acute pneumonia in A549 cells 18 . MiR‐155 regulates the immune response to bacterial pneumonia, 19 and miR‐21 may affect the function of macrophages to promote the occurrence and development of pneumonia 20 . Here, we found out a new miRNA, miR‐495, was downregulated in serum of patients with acute stage pneumonia, suggesting a potential therapeutical target in acute pneumonia.…”
Section: Discussionmentioning
confidence: 75%
“…18 MiR-155 regulates the immune response to bacterial pneumonia, 19 and miR-21 may affect the function of macrophages to promote the occurrence and development of pneumonia. 20 Here, we found out a new miRNA, miR-495, was downregulated in serum of patients with acute stage pneumonia, suggesting a potential therapeutical target in acute pneumonia. Generally, LPS, as the main pathogenic component of gram negative bacteria, 21 directly binds with monocyte or Toll like receptor 4 on macrophage, thus leading to the release of inflammatory cytokines, sepsis and pneumonia.…”
Section: Discussionmentioning
confidence: 75%
“…Staffed with experts trained in advanced diagnostics and patient care, neuro-ICUs address the complex needs of patients with nervous system damage, aiming to improve their ability to move and communicate. Neuro-ICUs, however, face challenges with patients post neurosurgery, who may develop pulmonary complications, necessitating frequent radiological exams that contribute to significant cumulative radiation doses [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%